The Relationship between Parental Rearing Behavior, Resilience, and Depressive Symptoms in Adolescents with Congenital Heart Disease - Moon, Ju Ryoung; Song, Jinyoung; Huh, June; Kang, I-Seok; Park, Seung Woo; Chang, Sung-A; Yang, Ji-Hyuk; Jun, Tae-Gook (Frontiers in Cardiovascular Medicine, 2017)
Objectives: Parental rearing behavior is one factor that influences the strength of resilience. In turn, resilience influences depression. However, it is unclear whether resilience has a mediating effect on the relationship between parental rearing and depression in adolescents with congenital heart disease (CHD). Therefore, the associations between parental rearing behavior and resilience and between rearing behavior and symptoms of depression were investigated with respect to age, gender and disease severity. Subjects and Methods: Patients completed a parental rearing behavior questionnaire, a resilience scale and the Child Depression Inventory during a routine clinic visit. Structural equation modeling with maximum likelihood estimation was used to analyze the data. Results: The median age of the 180 patients included in the study was 17.8 years, and 64% were male. Lower resilience was found to be associated with overprotection, punishment, rejection, and control. There was a strong relationship between resilience and symptoms of depression. Resilience varied according to gender, age group and disease severity. Conclusion: Parental rearing behaviors such as emotional warmth, rejection, punishment, control and overprotection have a significant influence on adolescent’s resilience. When developing intervention programs to increase resilience and reduce depression in adolescents with CHD, parenting attitudes, gender, age and CHD severity should be considered. Keywords: parental rearing behavior, resilience, depression, congenital heart disease.